Fretting Analysis of Aluminium 6061 Reinforced With Graphene - M.R, Srinivasa.; S Rammohan, Y; Irfan, Zahid (International Journal of Engineering and Technology, 2018)
The application of Aluminium alloys becomes significant and most wide in the field of aviation industry. Aluminium 6061, because of its pro mechanical characteristics. Graphene is one of the allotropic forms of Carbon which is abundantly available in nature. The high tensile strength and low density of graphene is the added advantage as it is used as a reinforced material with Aluminium 6061.  Graphene was found to be a more suitable reinforcing material that improves tribological properties of metal. Composite materials are mixtures of various parent materials resulting in the formation of materials having a mix of varied desired properties like low weight, larger stiffness, higher specific strength etc. The composite materials so obtained invariably have superior properties to their parental ones. So these materials become a really enticing notice for higher strengthened material for industrial sector. This paper primarily focuses on distinctive effects of utilizing Graphene as reinforcement for Al-6061in the view of tribological characteristics. Graphene has outstanding mechanical and physical properties, creating it a perfect reinforcement material for lightweight weight and high strength metal matrix composites (MMC) like Al-6061. Fabrication, being a important step, because it controls the microstructure, that successively determines the properties of the material, was conducted by stir casting. Stir casting additionally helped within the dispersion of Graphene uniformly within the metal matrix composite. To analyze the effect of tribological parameters damage resistance of the metal matrix composite, linear reciprocating tribometer was used.